2015
DOI: 10.1016/j.joco.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Survey of 274 patients with conjunctival neoplastic lesions in Farabi Eye Hospital, Tehran 2006–2012

Abstract: PurposeTo evaluate conjunctival epithelial neoplastic lesions in a 7-year period.Materials and methodsThe data of all primary cases of conjunctival neoplasia diagnosed in the Pathology Department of Farabi Eye Hospital were analyzed.ResultsThe patient group consisted of 179 (65.3%) males and 95 (34.6%) females, with an age range of 14–90 years and a mean age of 57.9 years. The most common primary conjunctival epithelial neoplastic lesion was invasive squamous cell carcinoma (SCC) (40.8%), followed by dysplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(40 reference statements)
2
5
0
2
Order By: Relevance
“…The prevalence of malignant conjunctival lesions in our study was 9%, comparable to the overall prevalence of malignant conjunctival lesions reported in previous studies [10,11,21]. In the current study, the most frequent malignant lesion was ocular surface squamous neoplasia (OSSN), which was observed in 5/10 adult specimens (50%), with no gender predilection; this finding is consistent with the findings of Elshazly and Aliakbar-Navahi et al [1,11], despite previous reports of a higher incidence of OSSN in males [7,[22][23][24]. The differences in the spectrum of OSSN could be attributed to racial and environmental factors, which was further illustrated in a study by Gichuhi et The clinical appearance of a lightly pigmented patch in a 30-year-old female that was excised without specific clinical diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of malignant conjunctival lesions in our study was 9%, comparable to the overall prevalence of malignant conjunctival lesions reported in previous studies [10,11,21]. In the current study, the most frequent malignant lesion was ocular surface squamous neoplasia (OSSN), which was observed in 5/10 adult specimens (50%), with no gender predilection; this finding is consistent with the findings of Elshazly and Aliakbar-Navahi et al [1,11], despite previous reports of a higher incidence of OSSN in males [7,[22][23][24]. The differences in the spectrum of OSSN could be attributed to racial and environmental factors, which was further illustrated in a study by Gichuhi et The clinical appearance of a lightly pigmented patch in a 30-year-old female that was excised without specific clinical diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…PAM z atypią rozpoznawano równie często u kobiet i u mężczyzn, PAM bez atypii natomiast częściej u mężczyzn (64%). W przypadku melanozy niezwykle ważne jest określenie atypii w badaniu histopatologicznym, ponieważ w od 12% do 50% przypadków PAM z atypią ma tendencję do transformacji w czerniaka (2,(13)(14)(15), podczas gdy PAM bez atypii nie wiąże się z ryzykiem transformacji nowotworowej (16). Niestety, klinicznie te zmiany są praktycznie nie do odróżnienia (16).…”
Section: Omówienieunclassified
“…Rak płaskonabłonkowy i dysplazja nabłonka częściej występowały u mężczyzn (66,7% i 83,3%), to jest zgodne z wcześniejszymi raportami (1,8,16). Tłumaczy się to większym narażeniem na promieniowanie UV mężczyzn niż kobiet (18). Ta grupa pacjentów była również najstarsza -średnia wieku ponad 60 lat.…”
Section: Omówienieunclassified
“…The presence of HPV has indeed been detected on the fingers of patients (37.5% of females, n = 3; 69% of males, n = 9) with genital warts [40], however the association between conjunctival and genital/anal papillomas is not clear. In a study of 17 women with HPV-related cervical dysplasia, DNA of HPV 16 was detected in both limbal and cervical swabs by polymerase chain reaction (PCR) in 35% of the patients [6], although no conjunctival papillomas were present [41]. Another study reported that coexistent genital warts and conjunctival papillomas was seen in 4% of patients (3 out of 73) [3].…”
Section: Main Textmentioning
confidence: 99%